Pery and Iberê: A Historical-Musicological Analysis of the Vocal Writing of Two Indigenous Characters on Stage: Uma análise histórico-musicológica da vocalidade de dois indígenas no palco (Orfeu, 2026)
Antônio Carlos Gomes was an opera composer active in Italy and Brazil between the 1870s and 1890s, a period during which Italian opera underwent some of its most significant transformations, culminating in the giovane scuola at the turn of the twentieth century. Among these transformations, the evolution of character vocality stands out—an aspect to which Gomes was anything but indifferent. This article offers a historical and musicological analysis of Gomes’s role in shaping two Indigenous primo uomo characters in his operas: Pery (Il Guarany, 1870), premiered in Milan, and Iberê (Lo Schiavo, 1889), premiered in Rio de Janeiro. The primary aim is to shed light on underexplored innovations by a Brazilian composer who remained closely aligned with the prevailing trends of Italian melodrama, thereby contributing to the scholarly understanding of the period. To achieve this, the study draws on research into the bel canto tradition and its transformations, incorporating literature on Verdi and Gomes’s contemporaries, critical reviews from the period, the composer’s correspondence with his performers, and nineteenth-century vocal pedagogy as articulated in treatises (Garcia, [year]; Giraldoni, [year]) as well as in the writings of Richard Miller (Miller, [year]; Miller, [year]). The findings reveal a composer of marked artistic individuality, confident in his creative direction. With Il Guarany (1870), Gomes anticipates a vocal idiom that would only reach full maturity in Otello (1887).